2009
DOI: 10.1093/jb/mvp111
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelium Expresses 3-Mercaptopyruvate Sulfurtransferase and Produces Hydrogen Sulfide

Abstract: Hydrogen sulfide (H(2)S) has been recognized as a smooth muscle relaxant. Cystathionine gamma-lyase, which is localized to smooth muscle, is thought to be the major H(2)S-producing enzyme in the thoracic aorta. Here we show that 3-mercaptopyruvate sulfurtransferase (3MST) and cysteine aminotransferase (CAT) are localized to vascular endothelium in the thoracic aorta and produce H(2)S. Both 3MST and CAT were localized to endothelium. Lysates of vascular endothelial cells produced H(2)S from cysteine and alpha-k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
335
0
13

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 430 publications
(354 citation statements)
references
References 23 publications
6
335
0
13
Order By: Relevance
“…R ecent evidence from CSE knockout mice suggests that loss of CSE gene expression results in a decrease in H 2 S production and a subsequent rise in blood pressure [16] . Furthermore, Shibuya et al and Olson et al showed that CSE, CBS, and 3MST were the three important H 2 S generating enzymes [13,14] . In our study, we found that the mRNA expression of 3MST in rat aorta was lower than that in the pulmonary artery, whereas the CSE protein was higher in the rat aorta than in the pulmonary artery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…R ecent evidence from CSE knockout mice suggests that loss of CSE gene expression results in a decrease in H 2 S production and a subsequent rise in blood pressure [16] . Furthermore, Shibuya et al and Olson et al showed that CSE, CBS, and 3MST were the three important H 2 S generating enzymes [13,14] . In our study, we found that the mRNA expression of 3MST in rat aorta was lower than that in the pulmonary artery, whereas the CSE protein was higher in the rat aorta than in the pulmonary artery.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that cystathinonine gamma-lyase (CSE), cystathionine beta synthase (CBS), and 3-mercaptopyruvate sulfurtransferase (3MST) are three H 2 S generating enzymes [13][14] . It is shown that H 2 S relaxes blood vessels and lowers blood pressure by opening ATP-sensitive K + channels in vascular smooth muscle cells [15] .…”
Section: Wwwchinapharcom Sun Y Et Almentioning
confidence: 99%
“…3-MST/CAT is localized in thoracic aorta ECs and produces H 2 S [13]; however, a vascular effect of 3-MST/CATderived H 2 S is unknown. Endogenous intra mitochondrial 3-MSTderived H 2 S has been shown to protect mitochondrial function/ metabolism [14].…”
Section: Introductionmentioning
confidence: 99%
“…Physiologically, H 2 S is generated from L-cysteine in reactions catalysed by three enzymes, including cystathionine-g-lyase(CSE), cystathionine-bsynthase(CBS) 1,2 and 3-mercap-topyruvatesulphurtransferase (3MST) 3 . Both CBS and CSE are localized to the cytoplasm, whereas 3MST is localized predominantly to the mitochondria.…”
mentioning
confidence: 99%
“…CSE is primarily responsible for most of the H 2 S production in the vasculature 4,5 , whereas CBS may be primarily responsible for H 2 S formation in the brain. H 2 S produced by 3MST regulates mitochondrial reactive oxygen species (ROS) production 3 . Intriguingly, the expression of H 2 S-generating enzymes and the endogenous production of H 2 S have recently been identified in male and female reproductive systems in several mammalian species [6][7][8][9][10][11] .…”
mentioning
confidence: 99%